TRANSFORMATIVE LEADERSHIP MODEL OF THE PRINCIPAL TO IMPROVE TEACHER PERFORMANCE AT MAFAZAH ISLAMIC JUNIOR HIGH SCHOOL, BOGOR - Saiful Falah; Ahmad Deas Ardiansyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This research was motivated by a lack of direction and motivation, as well as by the need to organize and evaluate the performance of Al-Qur'an teachers at Mafazah Islamic Middle School, Bogor. This research aims to ensure that school principals play a role in improving teacher performance through effective leadership. This research uses descriptive quantitative methods with a sample of 48 teachers. Data were collected through questionnaires and analyzed using validity, reliability, normality, linearity, and simple regression tests in SPSS 26. The results showed that the principal's leadership was charismatic, while the teacher's performance was in the medium category. The correlation test shows a significant relationship between principal leadership and teacher performance (sig 0.03), with a contribution of 17.4% (R square). In conclusion, the principal's leadership influences teacher performance, even though it is in the moderate category. More effective leadership strategies are needed to optimize the quality of Al-Qur'an learning.